Antibiosis effect of four banana and plantain cultivars on weevil (Cosmopolites sordidus Germar) in Kisangani, DR Congo - M.K. SONGBO; G. K. MONDE; B.D. DHED’A (Revue Marocaine des Sciences Agronomiques et Vétérinaires, 2019)
Antibiosis effect of four banana and plantain cultivars on weevil (Cosmopolites sordidus Germar) in Kisangani, DR Congo Black weevil (Cosmopolites sordidus Germar) development on bananas and plantains (Musa sp.) was assessed on four cultivars named Libanga likale (AAB), Litete (AAB), Lokusu (AAB) and Yangambi Km5 (AAA). Rearing black weevil with Litete cultivar has shown better insect growth expressed from most of parameters such as larvae number (31), adults emergence frequency (26.6), larvae′s mortality rate (14.1%) and post‐larvae development cycle (30 to 34 days) compared to Yangambi Km5 (9.3 larvae). Therefore, black weevil showed good response on plantains cultivars. Sex ratio (male: female) was similar among plantains cultivars but highly influenced in Yangambi Km5 with 1.8:1. Yangambi Km5 antibiosis showed high larvae mortality rate of 62.8%, weak emergency rate (9,3) and long post‐larvae development of 50 days. This shows that the cultivar ′Litete′ was the most susceptible to weevils.